PENGARUH LATIHAN ARM CURL PADA LENGAN TERHADAP KEMAMPUAN PUKULAN CLEAR BULUTANGKIS PADA ATLET CLUB PB. KINANTAN KABUPATEN TANAH DATAR - Utari, Silvia; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observations that have been made against the club athletes PB. Kinantan Tanah Datar when athletes do match, the athlete has the ability to punch clear look that is not maximized, because the shuttle cock who was hit hard not slide towards the opponent, shuttle cock with a slow rebound that will allow the opponent to return the shuttle cock. In addition and movement of bodies does still rigid in performing the technique. Relation to the matters punch clear if analyzing movement must be supported by physical abilities such as curl maximum arm strength, explosive power arm muscles and motor coordination dynamic and good body flexibility. The purpose of this study was to look at the effects of exercise on the arm of the arm curl punches clear ability badminton Athlete Club PB. Kinantan Tanah Datar. As the population used in this study is the Athlete Club PB. Kinantan Tanah Datar as many as 16 people. The sampling technique used is total sampling, so in this study sample is all population that is 16 people. The instrument used to collect data that Pree test and post test punch clear. The data obtained was analyzed using t-test. Based on the results of data analysis, Pree test and post-test, it appears that there is an average increase of 14.34% with a t test that t = 2,976> on the table = 1,753.Keywords: Exercise Arm In Arm Curl, Blow Clear Capabilities